2015
DOI: 10.1002/tea.21272
|View full text |Cite
|
Sign up to set email alerts
|

The effect of explicit environmentally oriented metacognitive guidance and peer collaboration on students' expressions of environmental literacy

Abstract: The prevalence of habitat and life-threatening environmental problems has motivated environmental researchers to develop education programs to strengthen students' environmental literacy. We argue that the connection between environmental literacy and metacognition is theoretically promising. Therefore, we developed the Meta-CIC model, which is designed to develop students' environmental literacy, in parallel to supporting their metacognition. The core of this model is open inquiry-based learning. An explicit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 135 publications
(202 reference statements)
0
20
0
Order By: Relevance
“…Here, as in other studies, it is likely that canopy cover is likely related to and perhaps acts in conjunction with other factors such as income and socio-economic status (see Table 1) and that it is likely not directly driving EL. Previous studies have shown that urban canopy cover is significantly correlated to the percentage of population with a bachelor's degree 23 . This is after adjusting for other landscape and population factors.…”
Section: Discussionmentioning
confidence: 98%
“…Here, as in other studies, it is likely that canopy cover is likely related to and perhaps acts in conjunction with other factors such as income and socio-economic status (see Table 1) and that it is likely not directly driving EL. Previous studies have shown that urban canopy cover is significantly correlated to the percentage of population with a bachelor's degree 23 . This is after adjusting for other landscape and population factors.…”
Section: Discussionmentioning
confidence: 98%
“…As metacognitive support is essential to open inquiry (Keselman, ; Minner et al., ), this support was embedded within the inquiry process. This metacognitive support was based on the Meta‐CIC model developed by Adler, Zion, and Mevarech (). The Meta‐CIC model combines an explicit metacognitive guidance ( Meta ) and peer collaboration in collaborating inquiry communities ( CICs ) within an inquiry‐based learning approach.…”
Section: Methodsmentioning
confidence: 99%
“…Peer collaboration is another promising strategy for providing scaffolding for students' problem solving (Johnson, 1988;Mergendoller et al, 2000;Adler, Zion & Mevarech, 2015). According to Ge and Land (2003), peer collaboration has two types: guided interaction and unguided interaction.…”
Section: The Design Of Internal Organization Structure From the Perspmentioning
confidence: 99%
“…Peer collaboration is another promising strategy for providing scaffolding for student problem solving (Johnson, 1988;Mergendoller, Bellisimo, & Maxwell, 2000;Adler, Zion, & Mevarech, 2015). Many existing problem-solving systems provided learning environments and communication tools to facilitate collaboration between students.…”
mentioning
confidence: 99%